Consequences of sport training during puberty - Roemmich, J. N.; Richmond, R. J.; Rogol, A. D. (2001)
Growth at puberty depends on one's genetic potential, nutritional status and a series of hormones. Energy expenditure may modify the effects of these three factors on the linear growth rate and the relative proportions of fat-free and fat mass. Participation in sports where weight control is not required does not seem to affect pubertal timing or alter linear growth rate. The growth and maturation of athletes in weight control sports have the additional burden of energy output greater than intake; however, in only a minority the energy deficit is great enough to slow growth and maturation. Studies focusing on male wrestlers and female gymnasts are reviewed. In the wrestlers the hormonal picture is consistent with mild-to-moderate GH resistance and perhaps mild maturational delay, especially in the lower weight classes. The deficits in lean body mass and fat mass "catch-up" quickly following the end of training and competitive season. The situation with the gymnasts is somewhat different, the goal being to develop muscular strength within a shorter and lighter physique. Marked under-nutrition can keep these adolescents pre-pubertal for many years of training and competition. Whether subsequent growth is disproportionate or not remains indeterminate, but the marked delay in the onset of estrogen action can permanently cause the skeleton to be under-mineralized. In conclusion, most athletes continue to track along the centiles of their genetic potential. To define the mechanisms of growth and maturational delay one must longitudinally study children in weight-control sports. J Endocrinol Invest 2001 Oct;24(9):708-15